2011
DOI: 10.7202/1005668ar
|View full text |Cite
|
Sign up to set email alerts
|

Braided Stories and Bricolaged Symbols: Critical reflection and transformative learning theory for teachers

Abstract: (imprimé) 1916-0666 (numérique) Découvrir la revue Citer cet article Brigham, S. (2011). Braided Stories and Bricolaged Symbols: Critical reflection and transformative learning theory for teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
(9 reference statements)
1
11
0
Order By: Relevance
“…In the current project, coaches met weekly and supported one another by sharing practices that both complemented and hampered the evolvement of their own practice and role. Consistent with Brigham's (2011) findings surrounding the transformative learning that occurred through the support that immigrant teachers provided one another, coaches in this study also grew in their thinking and emotional appreciation for one another. Although the coaches were in different places with respect to their growth and involvement in the classroom, they valued coming together and supporting each other in moving forward.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the current project, coaches met weekly and supported one another by sharing practices that both complemented and hampered the evolvement of their own practice and role. Consistent with Brigham's (2011) findings surrounding the transformative learning that occurred through the support that immigrant teachers provided one another, coaches in this study also grew in their thinking and emotional appreciation for one another. Although the coaches were in different places with respect to their growth and involvement in the classroom, they valued coming together and supporting each other in moving forward.…”
Section: Discussionsupporting
confidence: 81%
“…In Carrington and Selva (2010) reflective practice in conjunction with service-learning pedagogy demonstrated transformative learning in pre-service educators' perceptions of inclusive education, in which educators were able to reflect on and reconsider personal assumptions influencing practice and to change future pedagogy accordingly. Brigham (2011) studied the reflective responses of 24 immigrant educators (from 17 different countries) new to Canada who met in small groups on a regular basis to reflect and discuss issues surrounding immigration challenges and teaching. Results indicated that the educators identified a collective social transformation because of their involvement in the group.…”
Section: Theoretical Underpinnings and Backgroundmentioning
confidence: 99%
“…This exploratory essay is couched in transformative learning theory, which posits that people hold assumptions that can be challenged by influential events or engaging activities (Christie, Carey, Robertson, & Grainger, 2015;Mezirow, 1998). Nonthreatening discussions can encourage individuals to critically reflect on their own or others' viewpoints, thereby leading to altered perspectives and even attempted change (Brigham, 2011;Christie et al, 2015;Mezirow, 1998). Transformed thinking can, for example, result in efforts to create more favorable education or social practices (Carrington & Selva, 2010;Christie et al, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Transformed thinking can, for example, result in efforts to create more favorable education or social practices (Carrington & Selva, 2010;Christie et al, 2015). Transformative learning is thus inherently cognitive, affective, and social in nature (Brigham, 2011;Mezirow, 1998).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation